Development of Envirokal Booklet Media Based Problem Solving Material Environment Pollution - Tiffany, Tiffany; Pribadi, Tyas Agung; Tri Martuti, Nana Kariada (Journal of Biology Education, 2018)
The aim of the research is to know the worthiness and the effectiveness of Envirokal (Environment of Pekalongan) booklet with problem-solving method in the lesson of environmental pollution against student’s learning outcome. The research is done at Senior High School 3 Pekalongan with a Research and Development (R&D) design, with 10 steps of research starting from the needs assessment, until obtaining the final product, i.e. booklet. The assessment done by the experts shows that the Envirokal Booklet obtained high scores as and it was concluded that the Envirokal Booklet was very effective to be used as learning material and could increase the individual score and classical completeness.